Strategi peningkatan kinerja pegawai pada kantor Sekretariat DPRD Kota Pasuruan dalam prespektif Sumber Daya Manusia Islam: Strategy for improving employee performance at the Pasuruan City DPRD Secretariat office from an Islamic Human Resources perspective - Khomariyah, Lailatul; Titisari, Purnamie; Munir, Akhmad (IJABAH: Indonesian Journal of Sharia Economics, Business, and Halal Studies, 2025)
This study aims to examine human resources and practices that affect employee performance from the perspective of Islamic human resources. Employees of the Pasuruan City DPRD are the subject of research. The research method used is a qualitative approach and with a descriptive method, data collection techniques are carried out by interviews, observations, and documentation. Employee performance analysis is carried out by means of data reduction, data analysis, data verification, data preparation, conclusion drawn, validity check, and result reporting. The results of the study show that the strategy to improve employee performance in the secretariat consists of three main components. The first is Islamic-Based Training which includes religious activities such as Qur'an recitation and routine recitation every Friday, as well as the Friday Blessing program where employees are invited to give alms voluntarily. Second, Professionalism Development which includes training at Lemhanas, analysis of laws and regulations, and budget analysis. These programs are designed to improve employees' competencies and skills in various aspects of their careers, such as understanding of public policy, law, and financial management. Third, an Islamic Work Environment consisting of a Culture of Helping, in an Islamic work environment, the attitude of mutual assistance between employees is strongly emphasized. This culture creates a high sense of solidarity and care, increases productivity, and builds trust.